Dynamic multiple pattern detection algorithm - Khancome, Chouvalit; Boonjing, Veera (My University, 2010)
The multiple pattern matching has always been a significant principle for applying to a network security system. This principle is adapted to accommodate the target patterns to be detected in a pre-processing phase, and the objective text and the suspect patterns are simultaneously detected by comparing with the existing structure. This research article introduces a new algorithm of multi-string pattern matching by means of a new data structure called inverted lists. The inverted lists structure, inherited from the inverted index, is represented by the positions of characters which appear in the patterns. The new algorithm, which is more efficient time than the traditional algorithms, scans the given text in a single pass. More importantly, the structure of patterns is able to update the patterns over time. © 2010 IEEE.
Keywords: Inverted index; Inverted lists; Multiple pattern; Static dictionary matching; String matching